Análisis del proceso productivo en la panadería Dulcesa Sucursal la Ventura - Bravo Riasco, Génesis Tatiana (2020)
The Sweet Bakery is located in the Ventura sector dedicated to the production and commercialization of sweet and salt breads, as well as high quality desserts for the inhabitants of the city of Babahoyo and surrounding sectors, the growth is evident in recent years , a situation that brings with it a constant conflict within the production area since the processes do noto unfold normally, this study is developed in line of research on information and communication systems, entrepreneurship and innovation while the sub-line is local development and sustainable entrepreneurship and sustainable. The problems are due to the hiring of inexperienced personnel, poor condiciono of work tools and machinery, high rate of occupational risk, lack of adequate suppliers, reduced space, inadequate salaries, poor organizational climate, there are no stable schedules that are reflected in product quality and even in customer service, significantly affecting the image of the business.